Medical care of athletes for the Sydney 2000 Olympic and Paralympic Games - Krichton, K. J. (International SportMed Journal, 2000)
This article outlines the medical challenges to provide the best medical care to athletes, spectators, and staff at the Sydney 2000 Olympic and Paralympic Games. It emphasizes the enormous organization that this has involved to cover all aspects of medical care for the duration of the Games.